Phân tích đa thức thành nhân tử ( x2 +6x +5b) (x2-x +1) (x2 –x+2) -1

Question

Phân tích đa thức thành nhân tử ( x2 +6x +5b) (x2-x +1) (x2 –x+2) -1

in progress 0
Caroline 2 tuần 2021-07-08T20:01:48+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-08T20:03:03+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `a,x^2+6x+5`

    `=x^2+x+5x+5`

    `=x(x+1)+5(x+1)`

    `=(x+1)(x+5)`

    `b,(x^2-x+1)(x^2-x+2)-12`

    `=(x^2-x+3/2-1/2)(x^2-x+3/2+1/2)-12`

    `=(x^2-x+3/2)^2-1/4-12`

    `=(x^2-x+3/2)^2-49/4`

    `=(x^2-x+3/2+7/2)(x^2-x+3/2-7/2)`

    `=(x^2-x+5)(x^2-x-2)`

    `=(x^2-x+5)(x^2+x-2x-2)`

    `=(x^2-x+5)[x(x+1)-2(x+1)]`

    `=(x^2-x+5)(x+1)(x-2)`

    CHÚC BẠN HỌC TỐT

    0
    2021-07-08T20:03:44+00:00

    `a) x^2+6x+5`

    `=x^2+x+5x+5`

    `=x.(x+1)+5(x+1)`

    `=(x+1).(x+5)`

    `b) (x^2-x+1)(x^2-x+2)-12`

    `=(x^2-x+3/2-1/2).(x^2-x+3/2+1/2)-12`

    `=(x^2-x+3/2)^2-49/4`

    `=(x^2-x+3/2+7/2).(x^2-x+3/2-7/2)`

    `=(x^2-x+5).(x^2-x-2)`

    `=(x^2-x+5).(x^2+x-2x-2)`

    `=(x^2-x+5).[x(x+1)-2(x+1)]`

    `=(x^2-x+5).(x+1).(x-2)`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )